Hemodynamics, other cardiovascular parameters, and antihypertensive therapy effectiveness in primary arterial hypertension patients from various age groups - V. A. Lusov; E. M. Evsikov; N. V. Teplova; O. A. Baykova; A. A. Oshnokova (Кардиоваскулярная терапия и профилактика, 2010)
Aim. To investigate the parameters of central, intracardiac, and organ hemodynamics in various age groups, among the patients with previously diagnosed arterial hypertension (AH). Material and methods. The study included 1846 patients with primary AH of labile (borderline and Stage I AH) or stable (Stage II-III AH) clinical course, aged 16-72 years. Central and intracardiac hemodynamics parameters were assessed by echocardiography; carotid, suprapubic, and supraclavicular arteries were examined by Doppler ultrasound; retinal vessels – by ophthalmoscopy; renal arteries – by Doppler ultrasound and X-ray angiography; and abdominal aorta - by dynamic renal scintigraphy and Doppler ultrasound. Results. In patients with primary AH, older age correlated with higher systolic blood pressure (BP), decelerated heart rate, and lower diastolic BP. Hyperkinetic hemocirculation type was more common in patients with labile AH, combining with psychotic disturbances and syndromes; however, this type was not common in participants with stable AH. Conclusion. Antihypertensive therapy effectiveness and response were substantially lower in older patients with primary AH. In stable AH, this inverse association was less strong, possibly due to dominating renal and renovascular mechanisms of antihypertensive treatment resistance.